Students' Mathematical Communication: COVID-19 Problem-solving Experience Among High Achievers - Purbaningrum, Mayang; Lus Windyana Palupi , Evangelista (Pusat Studi Pengembangan Pembelajaran Matematika, 2022)
Mathematical communication skills are the ability to convey mathematical ideas, strategies, and solutions to solve mathematical problems, both written and verbal. The community must express ideas to solve mathematical problems in daily life or tell essential information, such as the news related to COVID-19. . The selection of subjects in this study used purposive sampling with the subjects of 3 high achievement students in ten grade. Subjects are selected based on the average daily test scores. Data collection was conducted by mathematical communication test using PISA liked problem uncertainty and data context about hand sanitizer and interview. The triangulation technique analyzed the result of test and interview data. The results showed that students with high achievement have high mathematical communication skills. Students with high achievement can present mathematical ideas orally and in writing, interpret and evaluate the strategy, the results obtained, and use terms, mathematical notation, and math symbols. Thus, high achievement students can communicate and solve problems in the context of COVID-19. This research provides new information about the mathematical communication of students with high mathematical abilities, so it can be one of the teacher's guidelines for determining appropriate learning to improve students' mathematical communication.